Comparison of the radiotoxicity of the 99mTc-labeled compounds 99mTc-pertechnetate, 99mTc-HMPAO and 99mTc-MIBI. (1st November 2016) - Maucksch, Ute; Runge, Roswitha; Wunderlich, Gerd; Freudenberg, Robert; Naumann, Anne; Kotzerke, Jörg
Abstract: Purpose: In addition to gamma radiation, 99m Tc emits low-energy Auger electrons with path-lengths of nanometers to micrometers that cannot be utilized for diagnostic procedures; however, they have frequently been discussed for therapeutic applications. We compared radiotoxicity of three 99m Tc-labeled radiopharmaceuticals with differences in the subcellular distribution. Materials and methods: The intracellular radionuclide uptake and subcellular distribution of [ 99m Tc]-pertechnetate ( 99m Tc-pertechnetate), [ 99m Tc]Tc-hexamethyl-propylene-aminoxime ( 99m Tc-HMPAO) and [ 99m Tc]Tc-hexakis-2-methoxyisobutylisonitrile ( 99m Tc-MIBI) were quantified in rat thyroid FRTL-5 cells. Radiotoxicity was compared using late phosphorylated histone H2AX (γH2AX) foci as a marker for unrepaired DNA double-strand breaks (DNA-DSB) and clonogenic cell survival. Results: 99m Tc-HMPAO showed a substantially higher uptake into the nucleus and the membrane/organelles than 99m Tc-pertechnetate or 99m Tc-MIBI. The colony-forming assay showed that 99m Tc-pertechnetate and 99m Tc-HMPAO caused a similar reduction in cell survival. 99m Tc-MIBI is less radiotoxic in terms of the estimated nucleus dose and induced the fewest number of γH2AX foci compared with the other 99m Tc-tracers, and 99m Tc-HMPAO induced a fewer number of γH2AX foci than 99m Tc-pertechnetate. Conclusions: Our findings reveal that clonogenic cellular survival is not solely determined by the DNA-DSB response. This finding may suggest the involvement of extra-nuclear radiosensitive targets in cell inactivation. For example, the mitochondria or the cell membrane could be affected by 99m Tc-HMPAO.